Psychogenic sensory loss: magnetic source imaging reveals normal tactile evoked activity of the human primary and secondary somatosensory cortex - Hoechstetter, Karsten; Meinck, Hans-Michael; Henningsen, Peter; Scherg, Michael; Rupp, André (Neuroscience letters, 2002)
We investigated the activation of the secondary somatosensory cortex (SII) in three patients with unilateral psychogenic sensory loss in the hand. Somatosensory evoked magnetic fields were recorded in response to tactile stimulation of the index finger of the affected and the unaffected hand. Brain sources were estimated by magnetic source imaging. In all subjects, responses in both the contralateral primary somatosensory (SI) and bilateral SII areas were normal as compared with a healthy control group, irrespective of the stimulated side. The results extend previous findings of normal evoked activity in SI.